Nutritional quality of amaranth (Amaranthus) silage in response to forage airing and addition of lactic bacteria = Calidad nutricional de amaranto (Amaranthus) ensilado en respuesta a la aireación del forraje y a la adición de bacterias lácticas - Zubillaga, María Fany; Repupilli, Julián Agustín; Boeri, Patricia Alejandra; Servera, Juan Agustin; Gallego, Juan Jose; Piñuel, Lucrecia (Facultad de Ciencias Agrarias, Universidad Nacional de Cuyo, 2025)
Climate change is reducing forage availability for ruminants. Previous studies in Northern Patagonia, Argentina, have demonstrated the adaptation of the amaranth crop to these agroclimatic conditions under irrigation. Moreover, this crop is used as forage in marginal areas of the world, given its outstanding productive and nutritional qualities. The objective of this study was to evaluate the nutritional quality of amaranth silage in response to previous wilting and the addition of lactic acid bacteria. The crop was harvested at the milky grain stage and ensiled in experimental microsilos for 60 days. Before ensiling, different treatments (wilting and addition of lactic acid bacteria) were applied. Parameters related to nutritional quality were evaluated, including ash, crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), dry matter digestibility (DMD), and metabolizable energy (ME). Simultaneous treatment with air and the addition of lactic acid bacteria before ensiling resulted in the best nutritional quality characteristics of the silage. The most significant results were protein value of 12.7%, 41.1% NDF and 19.1% FDA. The DM and ME were 74% and 2.67 Mcal/kg, respectively. Thus, amaranth silage can be considered an alternative conserved forage for animal feed in this region.